Femur Fracture Patient Characteristics in Dr. Hasan Sadikin General Hospital Bandung Indonesia January–December 2011 - Mohamad Firdaus; Nucki Nursjamsi Hidajat; Nani Murniati (Althea Medical Journal, 2015)
Background: Femur fracture is one of the most common orthopedic cases which may occur in all age groups. Its incidence can be characterized by several aspects, such as patient’s age, sex, causes, location and many more. The aim of this study was to understand the characteristics of femur fracture patients in Dr. Hasan Sadikin General Hospital Bandung Indonesia during the period of January to December 2011.Methods: A descriptive study was conducted using 89 medical records of femur fracture patients in the Department of Orthopedic and Traumatology Dr. Hasan Sadikin General Hospital Bandung from January to December 2011. The inclusion criteria of the study were medical records containing patient aged 20-59 years data who were diagnosed with femur fracture, sex, cause of fracture, type of fracture, location of fracture, type of treatments given, and the length of hospitalization. Data were analyzed using frequency distribution.Results: Of 60 cases of motor vehicle accidents, there were more male (77.53%) than female who suffered from fracture. Closed fracture was more common with 52 cases of closed fracture compared to 29 cases of proximal fracture. Of 35 patients accepted treatment, 30 patients were treated by surgery  and hospitalized for 21–30 days.Conclusion: Young male adults are the most common group suffering from femur fracture. A continuous epidemiology study must be carried out on annual basis so that a better view of the incidence and the location of femur fracture as well as the type of treatment given to patients can be observed.Keywords: Adults, characteristics, femur fracture  DOI: 10.15850/amj.v2n1.428